Minutes of General Council (extract)
017a-0035-001 G.C. -1 SEP. 1938 279. AUSTRALASIAN COUNCIL OF TRADE UNIONS. A telegram was received from the Australasian Council of Trade Unions, dated 18th August, 1938, as follows:- "Trade Unionists Australia through A.C.T.U. desire be associated any future move by Unionists Great Britain serving purpose lifting arms embargo against Spanish Government". NOTED. 292/946/17a/35